2016
DOI: 10.1371/journal.pone.0165323
|View full text |Cite|
|
Sign up to set email alerts
|

Linkage and Association Mapping for Two Major Traits Used in the Maritime Pine Breeding Program: Height Growth and Stem Straightness

Abstract: BackgroundIncreasing our understanding of the genetic architecture of complex traits, through analyses of genotype-phenotype associations and of the genes/polymorphisms accounting for trait variation, is crucial, to improve the integration of molecular markers into forest tree breeding. In this study, two full-sib families and one breeding population of maritime pine were used to identify quantitative trait loci (QTLs) for height growth and stem straightness, through linkage analysis (LA) and linkage disequili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…It is often more rapid and cost-effective than traditional linkage mapping. Linkage and association mapping are complementary approaches and are more similar than often assumed [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is often more rapid and cost-effective than traditional linkage mapping. Linkage and association mapping are complementary approaches and are more similar than often assumed [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies attempted GWAS for growth traits in forest trees, namely in Populus (Porth et al ., ; Allwright et al ., ; Du et al ., ; Fahrenkrog et al ., ), Pinus (Bartholomé et al ., ; Lu et al ., ) and Eucalyptus (Cappa et al ., ; Müller et al ., ; Resende et al ., ). Despite the considerably large number of individuals used in our study for each population and for the combined dataset, our results suggested that much larger numbers will be necessary to identify discrete regions capturing larger fractions of the genetic variance of complex traits as indicated by simulations (Spencer et al ., ; Visscher et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting reports on the genetic architecture of stem straightness in trees. For example, Bartholomé et al [63] detected QTLs that explained up to 5% of the total phenotypic variation of ST in maritime pine. Yang et al [64] found QTLs that explained up to 15% of the total phenotypic variation of the stem straightness of Pinus hybrids.…”
Section: Discussionmentioning
confidence: 99%